2016
DOI: 10.1590/2237-6089-2015-0064
|View full text |Cite
|
Sign up to set email alerts
|

Robin Williams' suicide: a case study

Abstract: Introduction: The world renowned comedian and four-time Oscar nominated actor Robin Williams died on August 11, 2014. From the outset, the news indicated that his death was believed to be a suicide and this was later confirmed to be true by the autopsy reports. Williams had been suffering from severe depression, which is believed to be the leading contributor to his suicide. In this case study, I will highlight the event of the actor's suicide and the main risk factors along with depression leading to his trag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The suicide of Robin Williams, who died on 11 August 2014 in his Californian home, provides a recent example of a celebrity suicide that was widely reported (Tohid, 2016), and several studies have examined the extent to which the media coverage conformed to relevant guidelines. In particular, a study by Carmichael and Whitley (2019) observed only moderate adherence to guidelines by US newspapers, noting that 46% of the articles they analysed provided details of the suicide method that Williams used (hanging), 27% romanticised his death and only 11% pointed readers to sources of help.…”
Section: Introductionmentioning
confidence: 99%
“…The suicide of Robin Williams, who died on 11 August 2014 in his Californian home, provides a recent example of a celebrity suicide that was widely reported (Tohid, 2016), and several studies have examined the extent to which the media coverage conformed to relevant guidelines. In particular, a study by Carmichael and Whitley (2019) observed only moderate adherence to guidelines by US newspapers, noting that 46% of the articles they analysed provided details of the suicide method that Williams used (hanging), 27% romanticised his death and only 11% pointed readers to sources of help.…”
Section: Introductionmentioning
confidence: 99%
“…20th/21st Century Actors: An examination of Jack Nicholson’s contributions to neuroscience and a discussion on Robin Williams’ suicide (Tripathi et al, 2017; Tohid, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The literature is filled with treatises on famous composers (Constant, 2011), writers (Jamison, 1989), poets (Hankir & Zaman, 2015), singers (Yip et al, 2006), actors (Tohid, 2016), and film directors (Dieguez, Assal & Bogousslavsky, 2007) who were troubled by various psychiatric and/or neurological diseases, and how these affected their lives and works. Not surprisingly, the visual arts could not be an exception to that rule.…”
Section: Introductionmentioning
confidence: 99%